Chiral Ammonium Salt Catalyzed Asymmetric Alkylation of Unactivated Amides - Xu, Changming; Yang, Xinshuang (Synlett, 2022)
A chiral spirocyclic quaternary ammonium salt catalyzed asymmetric alkylation of unactivated amides under homogeneous conditions has been developed, giving the target products with up to 60% ee. This novel methodology provides a general and concise protocol for asymmetric α-functionalization of unactivated amides.
Keywords: unactivated amides; asymmetric alkylation; homogeneous catalysis; kinetics control; ammonium salt catalyst